THE LANGUAGE OF PICTURES: THE ROLE OF TROPES IN THE FORMATION OF POETIC THINKING - Salikhova Nodira Nurullayevna (Bright Mind Publishing, 2025)
The article examines the significance of tropes as key elements that form poetic thinking and language picture of the world. The author analyses the functions of tropes in a fiction text, their role in creating imagery and expressiveness of speech, as well as the peculiarities of their use in Russian, Uzbek and English languages. Special attention is paid to cultural and linguistic differences in the understanding and translation of tropes, which is demonstrated by examples of literary works.
Keywords: Trope, metaphor, poetic thinking, linguistic picture of the world, Uzbek language, Russian language, imagery, stylistics, intercultural analysis, linguistic transference, artistic speech.